Cultura digital e fazer histórico: estudos dos usos e apropriações das tecnologias digitais de informação e comunicação no ofício do historiador - Aguiar, Leandro Coelho de (2012)
Tries to reconstruct the specific universe of historians the appropriation of new information and communication technologies (ICTs), in digital format, asking the possibilities that digital writing brings to the historigraphical from the identification and mapping of the research projects involving the production and appropriation of new technologies information and communication technologies in this format